Glucuronidation is the dominating in vivo metabolism pathway of herbacetin: Elucidation of herbacetin pharmacokinetics after intravenous and oral administration in rats. (January 2018) - Ge, Beikang; Zhao, Liang; Li, Xiaorong; Xu, Pingxiang; Xue, Ming
Abstract: The promising potential benefits of herbacetin in human entail its pharmacokinetic investigations, but the metabolic fate of this natural compound in vivo remains a field of unknown so far. The current study, for the first time, identified and quantified seven herbacetin-metabolites from rat urine, feces and bile after administration of herbacetin to rats. It was found that herbacetin was excreted primarily from rat urine in the form of glucuronide-conjugations. Subsequent in vitro enzyme kinetic studies and in vivo pharmacokinetic investigations suggested an extensive hepatic metabolism of herbacetin and the high exposure of herbacetin-glucuronides in systemic circulation. The clearance, t1/2 and bioavailability of herbacetin in rats were determined as 16.4 ± 1.92 ml·kg/min, 11.9 ± 2.7 min, and 1.32%, respectively. On basis of these findings, a comprehensive metabolic pathway of herbacetin in rats was composed, which was crucial for the further assessments of herbacetin therapeutic effects and mechanism of pharmacological action.